Give the devil his due [large type] - Hockensmith, Steve; Falco, Lisa, 1970- (Hockensmith, Steve. Tarot mystery., 2017)
"Reformed con artist-turned-tarot reader Alanis McLachlan gets paid for predicting the future--too bad she didn't see all the trouble in hers. First a figure from her past tries to drag her back into the life of crime she thought she'd left behind. Then a new suitor tries to sweep Alanis off her feet, forcing her on-again, off-again romance with hunky teacher Victor Castellanos to hit the skids. And then there's the little matter of the client who gets an ominous reading from Alanis ... and is promptly murdered. Danger is in the cards for Alanis, and she'll need all her skill at reading people and reading tarot if she's going to survive"--Amazon.com.